Integrating Critical Thinking into Indonesia's EFL Curriculum: Insights from Bengkulu Teachers - Adwitya Widya Dhari; Ira Maisarah (UNIB Press, 2025)
In today's globalized world, the ability to communicate effectively in English as a Foreign Language (EFL) and critical thinking are indispensable skills for Indonesian students. However, traditional EFL curricula in Indonesia often prioritize linguistic competence and neglect critical thinking skills. This study explores the perspectives of EFL teachers in Bengkulu regarding their students' critical thinking skills and their views on integrating critical thinking instruction into the EFL curriculum. Using two adapted questionnaires, data was collected from 23 teachers in various educational institutions in Bengkulu. The results showed that although students demonstrated basic critical thinking concepts, they struggled with higher-order skills such as evaluating evidence objectively and anticipating consequences. Most teachers (91.3%) believe that teaching critical thinking is part of their job, and 65.2% support its incorporation into the EFL curriculum. However, 65.2% felt that they needed more training, and 34.8% were unsure about what critical thinking entailed. These findings underscore the need for a comprehensive curriculum overhaul in which critical thinking is woven throughout the language domain, supported by extensive teacher training, localized learning materials, and innovative assessments. By undertaking such reforms, Indonesia can nurture a generation of globally competent communicators capable of navigating the complexities of the 21st century.